Theoretical analysis of the thermoelectric properties of penta-PdX2 (X = Se, Te) monolayer - Li, Lei; Huang, Zhuqin; Xu, Jinqi; Huang, Haihua (Frontiers in Chemistry, 2022)
Based on the successful fabrication of PdSe2 monolayers, the electronic and thermoelectric properties of pentagonal PdX2 (X = Se, Te) monolayers were investigated via first-principles calculations and the Boltzmann transport theory. The results showed that the PdX2 monolayer exhibits an indirect bandgap at the Perdew–Burke–Ernzerhof level, as well as electronic and thermoelectric anisotropy in the transmission directions. In the PdTe2 monolayer, P-doping owing to weak electron–phonon coupling is the main reason for the excellent electronic properties of the material. The low phonon velocity and short phonon lifetime decreased the thermal conductivity (κl) of penta-PdTe2. In particular, the thermal conductivity of PdTe2 along the x and y transmission directions was 0.41 and 0.83 Wm−1K−1, respectively. Owing to the anisotropy of κl and electronic structures along the transmission direction of PdX2, an anisotropic thermoelectric quality factor ZT appeared in PdX2. The excellent electronic properties and low lattice thermal conductivity (κl) achieved a high ZT of the penta-PdTe2 monolayer, whereas the maximum ZT of the p- and n-type PdTe2 reached 6.6 and 4.4, respectively. Thus, the results indicate PdTe2 as a promising thermoelectric candidate.